Ad hoc method for the assessment on listing and categorisation of animal diseases within the framework of the Animal Health Law. (7th July 2017) - ,; More, Simon; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortázar Schmidt, Christian; Michel, Virginie; Miranda, Miguel Angel; et al.
Abstract: The European Commission has requested EFSA to assess animal diseases according to the criteria as laid down in Articles 5, 7, 8 and Annex IV for the purpose of categorisation of diseases in accordance with Article 9 of the Regulation (EU) No 2016/429 (Animal Health Law). This scientific opinion addresses the ad hoc method developed for assessing any animal disease for the listing and categorisation of diseases within the Animal Health Law (AHL) framework. The assessment of individual diseases is addressed in distinct scientific opinions that are published separately. The assessment of Articles 5, 8 and 9 criteria is performed on the basis of the information collected according to Article 7 criteria. For that purpose, Article 7 criteria were structured into parameters and the information was collected at parameter level. The resulting fact sheets on the profile and impact of each disease were compiled by disease scientists. A mapping was developed to identify which parameters from Article 7 were needed to inform each Article 5, 8 and 9 criterion. Specifically, for Articles 5 and 9 criteria, a categorical assessment was performed, by applying an expert judgement procedure, based on the mapped information. The judgement was performed by EFSA Panel experts on Animal Health and Welfare in two rounds, individual and collective judgement. The output of the expert judgement on the criteria of Articles 5 and 9 for each disease is composed by the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. To take better account of the uncertainties involved, a quantitative instead of a categorical approach has been followed from 2021. The output henceforth consists in the individual probability ranges provided by the experts and their computed median range.